Exploring the Dimensionality of Digit Span. (April 2013) - Bowden, Stephen C.; Petrauskas, Vilija M.; Bardenhagen, Fiona J.; Meade, Catherine E.; Simpson, Leonie C.
The Digit Span subtest from the Wechsler Scales is used to measure Freedom from Distractibility or Working Memory. Some published research suggests that Digit Span forward should be interpreted differently from Digit Span backward. The present study explored the dimensionality of the Wechsler Memory Scale–III Digit Span (forward and backward) items in a sample of heterogeneous neuroscience patients ( n = 267) using confirmatory factor analysis (CFA) for dichotomous items. Results suggested that four correlated factors underlie Digit Span, reflecting easy and hard items in both forward and backward presentation orders. The model for Digit Span was then cross-validated in a seizure disorders sample ( n = 223) by replication of the CFA and by examination of measurement invariance. Measurement invariance tests of the precise numerical generalization of trait estimation across groups. Results supported measurement invariance and it was concluded that forward and backward digit span scores should be interpreted as measures of the same cognitive ability.